EcoLinguistic Insights in Nias Village Name: Unravelling the Dynamic Bond Between Language and Environment - Hadi, Wisman; Mulyono, Mulyono (REiLA : Journal of Research and Innovation in Language, 2023)
Ecological structures hold profound significance in the identification and naming of localities within Nias villages. This significance underscores the dynamic bond between language and the environment, forming a foundational aspect of the local ethnicity. This study endeavors to delve into the ecological significance that underpins the naming of Nias villages, elucidating the intricate connection between language and the environment upon which village names are founded. In pursuit of this objective, the research engages with a purposive sample of 20 informants, representing 151 localities within Nias. Through in-depth interviews, valuable insights are gathered and transcribed to constitute the research data. Employing a descriptive qualitative design, the study leverages a semantic representation protocol to categorize data according to the ecological units embedded in the village names. The investigation's findings reveal that the Nias villages predominantly employ the Nias language lexicon. Notably, 55 villages incorporate the lexicon "hili" denoting 'hill or mountain,' such as "Hilimbana" ('hill-kapuk tree') and "Hiliweto Gela" ('hill-bees'). Additionally, the names incorporate ecological elements such as vegetation, rivers, animals, equipment, events, supernatural objects, and numbers. These names reflect the deep integration of ecological elements into the local community's cultural identity and highlight the rich ecological diversity of the region. The study emphasizes the importance of understanding the cultural and ecological connections in village names for the preservation of Nias Regency's heritage and the promotion of ecological awareness. Further research avenues include exploring the socio-cultural significance of village names and investigating the impact of language on environmental conservation efforts. Understanding the intricate relationship between language, culture, and the environment is crucial for sustainable development and the preservation of cultural and ecological heritage in Nias Regency.